KONTRADIKSI KEBIJAKAN INDUSTRI KREATIF DAN USAHA PELESTARIAN KESENIAN TRADISI (Kasus Seni Pertunjukan Luambek) - Irfan Kurniawan (Besaung : Jurnal Seni Desain dan Budaya, 2016)
Arrival of social change comes as a result of the process of industrializationand globalization of information, if viewed from all aspects, influenced by such changes. One aspect is the art, from the influence of these changes, the art began to shift toward commercial dimension of art. So is the case in government policy on the development and preservation of art and culture, also insists on the principle of industrial and creative economy. The policy on the one hand, has a positive impact (in economic terms), but on the other hand also have a negative impact, namely the commercialization, commodification, and profane without considering the cultural assumptions. resulting in a decline in ethical values and aesthetic, and neglect the development and preservation of ritual art tradition in the context of the natural cultural community, because they are not going to bring benefits in terms of economy and creative industries.such as the deterioration condition of art performances luambek in Pariaman Minangkabau society. Contradictions creative industries policy and conservation efforts in the arts need special attention by the relevant parties, especially in preparing the formula the preservation of traditional art concepts in the context of supporting the community. Keyword: contradiction, creative industries and traditional arts